The "Mobile You" breathalyzer - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
The X275 Mobile You Breathalyzer is a portable, handheld breathalyzer device made by Youtoi Industries of Japan. Following successful marketing of the product in Japan, the company is expanding its focus to Germany. This case study presents a comparison of the Japanese and German markets and asks readers to consider how Youtoi should conduct its market research and whether it will be as successful in Germany as in Japan.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). The "Mobile You" Breathalyzer. In International marketing (pp. 221-222). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Marketing research -- Case studies; Export marketing -- Case studies